Effect of Land Use on Physical and Chemical Properties of Soil at Village -Chama (Ranchi) - Mahto, K.M. (Journal of Soil and Water Conservation, 2022)
On the basis of topographical situations, the soils of Chotanagpur have been divided into upland, Mediumland, and the land use is restricted accordingly. Due to undulating landscape, the erosion hazards of varying intensities are noticed and some of the lands have suffered so much that they are out of cultivation. From the review of literature it appears that there may be changes in the properties of the soil due to land use. For instant Bhaumik (1957) reported depletion of clay content in the soils of Chotanagpur due to indiscriminate use of land causing soil erosion. Handal (1957) observed differences in soil texture between up land and low land of Chotanagpur. Jenny and Ray Chaudhuri (1960) found higher organic matter content in the forest and paddy soil than under conti- nuous cropped soils. Gupta and Khanna (1964) observed eroded soil to be poor in organic and calcium bound phosphates.